2019
DOI: 10.1111/jpn.13234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous amylase on the in vitro digestion kinetics of whole‐crop maize silages made from flint or dent grain type at different phenological stages grown in tropical condition

Abstract: The effect of exogenous amylase on the in vitro rumen digestion kinetics of wholecrop maize silage made from dent (RB9004) or flint grain type (RB9308) was evaluated at different phenological stages: soft dough (SOD), early dent (EAD), ½ milkline (½M) and ¾ milkline (¾M). Forage was harvested from 70 to 110 days after sowing. Two rumen-cannulated cows receiving or not exogenous amylase (0.7 g/kg dry matter-DM, provided to achieve 396 kilo Novo units of amylase activity/kg of TMR DM) were used as donor of rumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…As the majority of corn genotypes used for silage production in this country is flint type, strategies regarding corn silage management should focus on the improvements of starch utilization. In this regard, the current study was designed to investigate how maturity, bacterial inoculation, and storage length interact with each other in flint corn silage to obtain high-quality silage with enhanced starch-D. Agronomic features (DM yield and percentage of grains) and nutritional characteristics of the corn crop used in this study were typical of those reported under Brazilian conditions ( Rabelo et al, 2015 ; Silva et al, 2020 ), with the exception of the NDF content, which had a slight increase as the maturity advanced rather than being diluted as a response of increasing percentage of grains in the whole-crop corn.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of corn genotypes used for silage production in this country is flint type, strategies regarding corn silage management should focus on the improvements of starch utilization. In this regard, the current study was designed to investigate how maturity, bacterial inoculation, and storage length interact with each other in flint corn silage to obtain high-quality silage with enhanced starch-D. Agronomic features (DM yield and percentage of grains) and nutritional characteristics of the corn crop used in this study were typical of those reported under Brazilian conditions ( Rabelo et al, 2015 ; Silva et al, 2020 ), with the exception of the NDF content, which had a slight increase as the maturity advanced rather than being diluted as a response of increasing percentage of grains in the whole-crop corn.…”
Section: Discussionmentioning
confidence: 99%